A study of heat - treatment effects on the aluminium alloys weldment - 272386 Zailee Dollah (Kuala Lumpur : Universiti Teknologi Malaysia, 1985)
Thesis (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1985